'Fighting a losing battle': prisoners' perspectives of treatment as prevention for hepatitis C with inadequate primary prevention measures. (2nd November 2019) - Lafferty, Lise; Rance, Jake; Treloar, Carla; ,
Abstract: Hepatitis C virus (HCV) is a global public health concern. Prisoners are particularly affected, with high prevalence and ongoing HCV transmission. The Surveillance and Treatment of Prisoners with hepatitis C (SToP-C) study is implementing the first trial of HCV treatment as prevention (TasP) in the prison setting, i.e., scaling up treatment at sufficient scale to achieve a preventive effect. This qualitative sub-study sought to explore prisoners' perceptions of feasibility of TasP. Participants were recruited from four correctional centres in New South Wales, Australia, including one women's prison. Thirty-two prisoners with a history of injecting drug use participated in interviews prior to prison-wide HCV treatment scale-up. All participants had been screened for HCV within the previous 6 months; half ( n = 16) had chronic HCV; n = 2 were awaiting test results. Concerns regarding prisoner movements (e.g. transferred to another prison, or incarceration-release-incarceration) and perceived subsequent risks for HCV reinfection were consistently raised as a major challenge for TasP elimination efforts. Suggestions for harm reduction measures to assist TasP effectiveness (and reduce risk of re-infection) included education and prison needle syringe programmes. Prisoners remain concerned about long-term effectiveness of TasP efforts without access to effective prevention measures and subsequent risk of (re-)infection.